Gloora gen. nov. (Lepidoptera: Erebidae: Arctiinae: Arctiini: Ctenuchina) for several Agylla-like Arctiinae - Grados, Juan; Laguerre, Michel; Boppré, Michael (Zootaxa, 2018)
Gloora gen. nov. is established for Eucereon alba (Druce, 1894), Hyaleucerea mundula (Berg, 1882), Agaraea sericeum (Zerny, 1931), and Gloora canae sp. nov. These species are (re‑)described considering male genitalia in particular and, in case, barcodes. Further species which might fit into Gloora gen. nov. are discussed.